Pattern of Micro Enterprises Accounting Records and The Barriers - Putri Wulanditya (Journal of Economics, Business, and Accountancy Ventura, 2018)
This study focuses on the micro-scale enterprises. The motivation of this study is to assist the parties in direct contact in order to know how the pattern of accounting records that had been done by the practitioners of SMEs is and what barriers they had experienced related to the production of financial statements simple. This study included in the exploratory study, collected data through interview, observation and documentation. The results of the study at 38 micro business unit showed 58% had evidence of financial transactions, but only 28% who take records of these transactions either into the cash book and the sales book. Some of the obstacles faced by entrepreneurs include difficulty separating personal wealth and their business interests, evidence of transactions forget to be stored, for trade and manufacturing businesses having problems calculating inventory and cost of sales.